Viability, economic transition and reflection on neoclassical economics - Justin Yifu Lin (Transformation, Integration and Globalization Economic Research (TIGER), 2004)
Many transition policies, based on neoclassical economics, failed in Eastern Europe, the former Soviet Union, and China. This paper argues that the failure is due to the viability assumption in neoclassical economics. Neoclassical economics implicitly assumes that a firm is expected to earn a socially acceptable profit in an open, competitive market as long as the firm has normal management. However, many firms in the socialist as well as transitional economies are not viable, that is, they will not be able to earn a socially acceptable profit in an open, competitive market even if they are under normal management because they are in sectors that are inconsistent with their economies' comparative advantages. Under the viability assumption, reform policies, based on neoclassical economics, focus on issues related to property rights, corporate governance, government interventions and other issues that may obstruct a firm's normal management. However, many of those issues are in fact endogenous to the firms' viability problem. Therefore, without addressing the firms' viability problem, those reforms fail to achieve their intended goals. Not only in the socialist and transition economies but also in many developing economies there exist many nonviable firms. This paper suggests that the viability assumption in neoclassical economics to be relaxed when analyzing issues in socialist, transition and developing economies.
Keywords: 330; Neoklassische Theorie; Systemtransformation; Systemtransformation; China; Theorie